Mean Platelet Volume (MPV): New Perspectives for an Old Marker in the Course and Prognosis of Inflammatory Conditions - Korniluk, Aleksandra (Mediators Inflamm, 2019)
Platelet size has been demonstrated to reflect platelet activity and seems to be a useful predictive and prognostic biomarker of cardiovascular events. It is associated with a variety of prothrombotic and proinflammatory diseases. The aim is a review of literature reports concerning changes in the mean platelet volume (MPV) and its possible role as a biomarker in inflammatory processes and neoplastic diseases. PubMed database was searched for sources using the following keywords: platelet activation, platelet count, mean platelet volume and: inflammation, cancer/tumor, cardiovascular diseases, myocardial infarction, diabetes, lupus disease, rheumatoid arthritis, tuberculosis, ulcerative colitis, renal disease, pulmonary disease, influencing factors, age, gender, genetic factors, oral contraceptives, smoking, lifestyle, methods, standardization, and hematological analyzer. Preference was given to the sources which were published within the past 20 years. Increased MPV was observed in cardiovascular diseases, cerebral stroke, respiratory diseases, chronic renal failure, intestine diseases, rheumatoid diseases, diabetes, and various cancers. Decreased MPV was noted in tuberculosis during disease exacerbation, ulcerative colitis, SLE in adult, and different neoplastic diseases. The study of MPV can provide important information on the course and prognosis in many inflammatory conditions. Therefore, from the clinical point of view, it would be interesting to establish an MPV cut-off value indicating the intensity of inflammatory process, presence of the disease, increased risk of disease development, increased risk of thrombotic complications, increased risk of death, and patient's response on applied treatment. Nevertheless, this aspect of MPV evaluation allowing its use in clinical practice is limited and requires further studies.